2022
DOI: 10.1186/s12885-022-09644-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of pegylated recombinant human granulocyte colony-stimulating factor during concurrent chemoradiotherapy for small-cell lung cancer: a retrospective, cohort-controlled trial

Abstract: Objective To investigate pegylated recombinant human granulocyte colony-stimulating factor (PEG-rhG-CSF) safety and efficacy in preventing hematological toxicity during concurrent chemoradiotherapy (CCRT) for small-cell lung cancer (SCLC). Methods We retrospectively assessed 80 SCLC patients treated with CCRT from January 2013 to December 2018 who received PEG-rhG-CSF within 48 hours after the end of chemotherapy, defined as prophylactic use, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The results showed that the experimental group had a significantly lower incidence of grade 3/4 neutropenia (23.75% vs. 67.5%) and FN (2.5% vs. 16.25%) than the control group, without significant acute esophagitis or pulmonary toxicity 34 . However, the prophylactic administration of PEG‐rhG‐CSF did not confer a significant survival benefit to patients 34 . Apart from thoracic tumors, evidence supporting pelvic radiotherapy, such as CCRT for cervical cancer, is also gradually increasing.…”
Section: Efficacy and Safety Of Peg‐rhg‐csf During Ccrtmentioning
confidence: 92%
See 4 more Smart Citations
“…The results showed that the experimental group had a significantly lower incidence of grade 3/4 neutropenia (23.75% vs. 67.5%) and FN (2.5% vs. 16.25%) than the control group, without significant acute esophagitis or pulmonary toxicity 34 . However, the prophylactic administration of PEG‐rhG‐CSF did not confer a significant survival benefit to patients 34 . Apart from thoracic tumors, evidence supporting pelvic radiotherapy, such as CCRT for cervical cancer, is also gradually increasing.…”
Section: Efficacy and Safety Of Peg‐rhg‐csf During Ccrtmentioning
confidence: 92%
“…18 Moreover, no significant differences were observed in radiation-related toxicity, treatment-related mortality rates, or sur- than the control group, without significant acute esophagitis or pulmonary toxicity. 34 However, the prophylactic administration of PEG-rhG-CSF did not confer a significant survival benefit to patients. 34 Apart from thoracic tumors, evidence supporting pelvic radiotherapy, such as CCRT for cervical cancer, is also gradually increasing.…”
Section: Head and Neck Tumorsmentioning
confidence: 97%
See 3 more Smart Citations